Microfluidic Nanobioplatform-Based Immunosensor for Monitoring of 25-Hydroxy Vitamin-D3 - Deepika Chauhan; Zimad Hashmi; Rishi Raj; Pratima R. Solanki (ECS Sensors Plus)
Measurement of 25-hydroxyvitamin-D _3 (25-VitD _3 ) is crucial because its deficiency is linked to a variety of disorders, including osteoporosis, diabetes, depression, some autoimmune conditions, and even Covid-19. Hence, it is important to find new methods for efficient rapid testing for clinical diagnosis and public health prevention. Here, a new nanomaterial-based microfluidic electrochemical immunosensor towards the determination of 25-VitD _3 using microwave synthesized gadolinium oxide nanoparticles (GdNPs) is presented. Mask-less lithography was used to create a micro-fluidic nano-bioplatform (MNBP) and three-electrode immunosensor on a transparent indium tin oxide (ITO) coated glass substrate. To fabricate MNBP (BSA/AB-25VitD _3 /CS@GdNPs/ITO), the working electrodes were functionalized with GdNPs, AB-25VitD _3 , and BSA (bovine serum albumin) in that order. The electrochemical response induced by the immunocomplex was measured in individual 25-VitD _3 concentrations (1–100 ng ml ^−1 ). This immunosensor exhibited a higher sensitivity of 5.99 ng ml ^−1 , limits of detection of 4.5 ng ml ^−1 , and an analysis time of 30 min. In addition, clinical serum samples from three healthy people were used to validate the MNBP-based immunosensor, which showed a strong correlation with traditional enzyme-linked immunosorbent assays. The use of proposed immunosensor to serum samples would allow early detection of 25-VitD _3 deficiency, particularly in rural and resource-constrained settings.